Malaysia and Indonesia maritime connectivity and domestic political economic development amid pandemic COVID-19 - Hanizah Idris,; Chong, Wu Ling (Penerbit Universiti Kebangsaan Malaysia, 2021)
Southeast Asia is a vast economic region with a total population more than 600 million. The region provides a huge market and opportunity for countries in the region to achieve economic growth. The Belt and Road Initiative (BRI) has been proposed by China PDR in 2013 where some of Southeast Asian countries are the recipient of the investment projects including Malaysia and Indonesia. Together with Master Plan on ASEAN Connectivity (MPAC), both BRI and MPAC projects aim to improve physical connectivity, institutional connectivity and empowered people-to-people connectivity. This study examines how Malaysia and Indonesia have responded and participated in the BRI and MPAC in the aspect of their maritime connectivity and the development of related infrastructure. The early findings indicated that in comparison with Malaysia, Indonesia has been slow and cautious in embracing the BRI due to inefficiency in infrastructure development, various red tape and long-time anti-Chinese sentiments. The outbreak of coronavirus disease (COVID-19) that has been going back since December 2019 has severely hindered the progress of the maritime connectivity projects in both countries.